THE DEVELOPMENT OF A LEARNER-CENTERED LEARNING MANAGEMENT MODEL IS IMPORTANT FOR IMPROVING STUDENTS’ ACADEMIC ACHIEVEMENT - Campachat, Winai; Ruttanawijit, Peera; Rattanawijit, Nattakarn; Boriboonsap, Wittaya (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aimed to develop a model for developing student-centered learning management to improve students’ academic achievement. The research was conducted using the research and development process, with 4 steps. Step 1: Study the basic information of the school about the problem, causes of the problem, and solutions for students’ academic achievement from student learning documents in the academic year 2021. The tool used was a document record form, and content analysis was performed. Step 2: Create and develop the model, then draft and check the validity, appropriateness, feasibility, and usefulness of the model and manuals with an expert seminar, using meeting records and content analysis. Step 3: Try out the model with 12 teachers and 145 students at Ban Nong Prue School under the Sa Kaeo Primary Educational Service Area Office 1 in the academic year 2023. The tools used were an achievement test and a summary record of student academic achievement. Data were analyzed with basic statistics: percentage, mean, and standard deviation. Step 4: Evaluate the model by 17 users. The tool used was an evaluation form for appropriateness, practical feasibility, and usefulness. Data were analyzed using basic statistics: mean and standard deviation. The research results found that: 1) The problem and cause of academic achievement in 8 learning areas of students did not pass the set criteria. The cause was that teachers lacked knowledge and behaviors about student-centered learning management. The solution is teacher development. 2) The model has 4 components: principles, objectives, development process, and measurement and evaluation. The accompanying documents, including a manual for school directors and a manual for teachers, had validity, appropriateness, practical feasibility, and usefulness. 3) The trial of the model with Ban Nong Prue School in the academic year 2023 found that teacher and student quality passed the set criteria. 4) The evaluation of the model and accompanying documents was overall at the highest level, including practical feasibility, appropriateness, and usefulness.